2018
DOI: 10.3390/nu10081047
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Whole-Blood Gene Expression in the Norwegian Women and Cancer Post-Genome Cohort

Abstract: Norwegians are the second highest consumers of coffee in the world. Lately, several studies have suggested that beneficial health effects are associated with coffee consumption. By analyzing whole-blood derived, microarray based mRNA gene expression data from 958 cancer-free women from the Norwegian Women and Cancer Post-Genome Cohort, we assessed the potential associations between coffee consumption and gene expression profiles and elucidated functional interpretation. Of the 958 women included, 132 were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
(62 reference statements)
2
6
0
Order By: Relevance
“…The medium preference group exhibited a modest decrease in caffeine preference from the continuous access period to the intermittent access period. In humans, similar populations of caffeine drinkers have been distinguished (Goncalves et al, 2017;Barnung et al, 2018;Mitchell et al, 2014;Kuang et al, 2018;Cornelis, 2019). Interestingly, the amount of caffeine that was consumed in the different preference groups in the present study were similar to amounts of caffeine that are consumed in different groups of humans who drink caffeinated beverages.…”
Section: Discussionsupporting
confidence: 67%
“…The medium preference group exhibited a modest decrease in caffeine preference from the continuous access period to the intermittent access period. In humans, similar populations of caffeine drinkers have been distinguished (Goncalves et al, 2017;Barnung et al, 2018;Mitchell et al, 2014;Kuang et al, 2018;Cornelis, 2019). Interestingly, the amount of caffeine that was consumed in the different preference groups in the present study were similar to amounts of caffeine that are consumed in different groups of humans who drink caffeinated beverages.…”
Section: Discussionsupporting
confidence: 67%
“…On the other hand, systematic review by Paiva et al showed the absence of changes in C-reactive protein concentration after coffee consumption and decreased concentration after caffeine intake [17]. Changes in the expression of genes, especially those involved in inflammation in human, animal, and in vitro models [18,19,20], were reported. According to one of the animal studies, bean roasting affected the anti-inflammatory and antioxidant properties of coffee [21].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of coffee intake on gene expression and the lipidome were investigated by Barnung et al [ 16 ] and Kuang et al [ 17 ], respectively. Barnung et al [ 16 ] reported on the results from a population-based whole-blood gene expression analysis of coffee consumption that pointed to metabolic, immune, and inflammation pathways. Using samples from a controlled trial of coffee intake, Kuang et al [ 17 ] reported that coffee intake led to lower levels of specific lysophosphatidylcholines.…”
mentioning
confidence: 99%